Bamboo-based spinning materials and their preparation methods
By constructing a gradient interface reinforcement system for multimorphic bamboo-based fillers and a silane coupling reaction compatibility strategy, the problems of polylactic acid brittleness and poor interfacial compatibility with bamboo-based fillers were solved, achieving efficient toughening and reinforcement and stable melt spinning of bamboo-based spinning materials, and preparing biodegradable fibers with excellent comprehensive performance.
Patent Information
- Application Number
- CN202610507039.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-16
- Publication Date
- 2026-05-26
AI Technical Summary
Existing technologies have not yet provided a systematic solution that can simultaneously address the brittleness of polylactic acid, the poor interfacial compatibility of bamboo-based fillers, and the insufficient processability of melt spinning, making it difficult to meet the requirements for the softness and biodegradability of textile fibers.
By constructing a multi-morphological bamboo-based filler gradient interface reinforcement system, synergistic interface engineering of silane coupling and epoxy reaction compatibility, and a strategy of regulating crystallization kinetics through heterogeneous nucleation of bamboo nanocellulose, bamboo-based fillers are treated with aminosilane coupling agents and combined with poly(adipate adipate/butyl terephthalate) toughening agents and bamboo nanocellulose to form chemically bridged and grafted copolymers, achieving efficient toughening and reinforcement and stable melt spinning of polylactic acid-based composite materials.
The prepared bamboo-based spinning material has high tensile strength, elongation at break and good hand feel. Its comprehensive performance is comparable to that of petroleum-based polyester, and it is completely biodegradable, meeting the application requirements of the textile industry.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer composite materials technology, specifically relating to a spinning material and its preparation method, which uses polylactic acid and poly(butylene adipate / terephthalate) as matrix resins and multimorphic bamboo-based fillers as reinforcing and modifying components. Background Technology
[0002] Petroleum-based polyester fiber, as the world's largest-produced synthetic fiber, is widely used in clothing fabrics, home textiles, and industrial textiles. However, the production of polyester fiber is highly dependent on petroleum resources, and its degradation cycle in the natural environment after disposal can take hundreds of years, causing serious environmental pollution and ecological burden. Developing bio-based fiber materials derived from renewable resources to replace petroleum-based polyester has become an important research direction in the field of textile materials.
[0003] Polylactic acid (PLA) is an aliphatic polyester produced by fermentation and polymerization of plant starches such as corn and cassava. It is fully biodegradable and possesses good mechanical strength. PLA fibers have tensile strength and elastic modulus similar to polyester fibers and exhibit natural antibacterial and skin-friendly properties, making them an ideal candidate material to replace polyester. However, PLA has inherent defects such as poor toughness, low elongation at break, and slow crystallization rate, resulting in a narrow melt spinning processing window. The fibers produced are brittle and have a rough, stiff feel, severely limiting its large-scale application in the textile industry.
[0004] To overcome the brittleness of polylactic acid (PLA), existing technologies generally employ a blending toughening strategy. Chinese patent CN105694400B discloses a method for producing a PLA-bamboo powder composite modified material, which involves blending bamboo powder with PLA, a nucleating agent, a coupling agent, and a polycaprolactone toughening agent through granulation. The resulting material exhibits mechanical properties close to those of pure PLA. However, this technology is only geared towards injection molding and does not address spinning processes. Furthermore, the use of polycaprolactone as a toughening component results in limited toughening effects, with the increase in elongation at break insufficient to meet the softness requirements of textile fibers. Chinese patent CN106832989A discloses a bamboo-based biodegradable composite material for extrusion, using bamboo powder and PLA as the main materials, combined with maleic anhydride-grafted polyethylene as a compatibilizer. However, maleic anhydride-grafted polyethylene itself is non-biodegradable, compromising the material's fully degradable characteristics. Moreover, this approach also only targets extruded products and does not address fiber-grade applications. Chinese patent CN115028976B discloses a polylactic acid blend material with stereocomposite interface compatibilization. The compatibilization is achieved by introducing stereocomposite crystals at the interface between polylactic acid and poly(adipate) / butyl terephthalate. The prepared blend material has both strength and toughness. However, this technology does not introduce any plant-based fillers, so it cannot effectively increase the biomass content, nor does it involve the optimization of spinning process parameters.
[0005] Bamboo, a widely distributed, fast-growing, and renewable resource in China, has a cellulose content exceeding 60%, and bamboo fiber possesses natural antibacterial properties and excellent mechanical properties. Introducing bamboo-based materials into a polylactic acid (PLA) matrix can simultaneously achieve reinforcement modification and increase biomass content. However, a serious interfacial compatibility problem exists between the hydrophilic surface of bamboo-based materials and the hydrophobic matrix of PLA; direct blending leads to a sharp decline in the material's mechanical properties. Existing interfacial modification schemes mostly employ single coupling agent treatment or simple alkali treatment, resulting in limited modification effects and failing to meet the stringent requirements of spinning processing for material uniformity and rheological properties.
[0006] In summary, the existing technology has not yet provided a systematic solution to the triple technical challenges of polylactic acid brittleness, poor interfacial compatibility of bamboo-based fillers, and insufficient processability of melt spinning. There is an urgent need to develop a polylactic acid / bamboo-based composite material for spinning applications and its preparation method. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of the prior art and provide bamboo-based spinning materials and their preparation methods. By constructing a multi-morphological bamboo-based filler gradient interface reinforcement system, silane coupling and epoxy reaction compatibility synergistic interface engineering, and bamboo nanocellulose heterogeneous nucleation regulation crystallization kinetics strategy, efficient toughening and reinforcement and stable melt spinning processing of polylactic acid-based composite materials are achieved. The mechanical properties and softness of the produced fibers are comparable to those of petroleum-based polyester, and they are completely biodegradable.
[0008] To achieve the above objectives, this invention provides a bamboo-based spinning material, which, by weight, comprises 45-65 parts polylactic acid, 20-40 parts modified bamboo-based filler, 5-15 parts poly(butylene adipate / terephthalate), 1-3 parts glycidyl methacrylate, 0.5-1.5 parts aminosilane coupling agent, 0.1-0.5 parts antioxidant, 0.2-0.8 parts heat stabilizer, and 1-4 parts bamboo nanocellulose. The modified bamboo-based filler is a mixture of bamboo micropowder and bamboo short fibers surface-treated with an aminosilane coupling agent. The bamboo micropowder has a particle size of 10-20 micrometers, and the bamboo short fibers have a length of 1-3 millimeters and a diameter of 10-50 micrometers. The bamboo nanocellulose has a particle size of no more than 100 nanometers and a solid content of 10%-20%.
[0009] The present invention also provides a method for preparing the above-mentioned bamboo-based spinning material, comprising four process stages: surface modification of bamboo-based filler, pre-drying of polylactic acid and poly(adipate) / butyl terephthalate, twin-screw extrusion blending and granulation, and melt spinning.
[0010] The beneficial effects of this invention are as follows: First, in the multi-morphological bamboo-based filler gradient reinforcement system, bamboo micropowder fills the matrix voids and provides uniform stress dispersion nodes, bamboo short fibers bear tensile loads along the orientation direction, and bamboo nanocellulose forms a network entanglement structure in the polylactic acid matrix and acts as a heterogeneous nucleating agent to significantly accelerate polylactic acid crystallization. The synergistic effect of the three bamboo-based components at different scales achieves full-scale interface reinforcement from nanometer to millimeter. Second, in the synergistic interface engineering strategy of aminosilane coupling agent and glycidyl methacrylate, the amino end of the aminosilane coupling agent forms hydrogen bonds and covalent bonds with the hydroxyl groups on the surface of the bamboo-based material, and the siloxane end undergoes a condensation reaction with the polylactic acid matrix, establishing a chemical bridge between the bamboo-based filler and polylactic acid; the epoxy functional group of glycidyl methacrylate undergoes a ring-opening reaction with the carboxyl end of polylactic acid and the hydroxyl end of poly(adipic acid / butyl terephthalate) during melt processing to form a graft copolymer, effectively compatibilizing the two-phase interface and significantly improving the elongation at break and impact toughness of the material. Third, the tensile strength of the produced fiber can reach more than 35 MPa, the elongation at break can reach more than 25%, the fiber has a soft hand feel, and its comprehensive performance is comparable to that of petroleum-based polyester. Moreover, all components are biodegradable. Detailed Implementation
[0011] The present invention will be described in detail below with reference to specific embodiments. All raw materials used in the following embodiments are commercially available products. Polylactic acid (PLA) is selected as spinning-grade granules with a melt index of 30-60 g / 10min (190°C / 2.16kg), a purity of not less than 99%, and a melting point of 175-185°C. Poly(butylene adipate) / terephthalate (PAT) is selected as commercial-grade granules with a melt index of 2-5 g / 10min (190°C / 2.16kg) and an elongation at break of not less than 500%. Bamboo micro-powder has a particle size of 10-20 micrometers, a moisture content of not more than 3%, and an ash content of not more than 2%. Bamboo short fibers have a length of 1-3 mm, a diameter of 10-50 micrometers, a moisture content of not more than 3%, and a fiber integrity of not less than 90%. Bamboo nanocellulose has a particle size of not more than 100 nanometers and a solid content of 10%-20%. The aminosilane coupling agent selected is KH-550 with a purity of not less than 98%. The glycidyl methacrylate used is a product with a grafting rate of not less than 1.5%. The antioxidant used is pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], with a heat resistance of not less than 300°C. The heat stabilizer used is a calcium / zinc stearate composite stabilizer with a purity of not less than 99% and free of heavy metals.
[0012] Example 1 This embodiment provides an optimal formulation scheme and preparation method for bamboo-based spinning materials.
[0013] The formula composition by weight is as follows: 55 parts polylactic acid, 25 parts modified bamboo micro powder, 5 parts modified bamboo short fiber, 10 parts poly(butylene adipate / terephthalate), 1.5 parts glycidyl methacrylate, 2.7% (0.8 parts) of aminosilane coupling agent KH-550 by weight of total bamboo-based filler, 0.3 parts antioxidant, 0.4 parts heat stabilizer, and 2 parts bamboo nanocellulose.
[0014] Surface modification of bamboo-based fillers: Bamboo micropowder and bamboo short fibers were placed separately in a hot air drying oven and dried at 105°C for 3 hours to reduce the moisture content to below 3%. A 5% (w / w) KH-550 ethanol solution was prepared. The dried bamboo micropowder and bamboo short fibers were separately added to a high-speed mixer and operated at 800 rpm. Simultaneously, the KH-550 ethanol solution was uniformly sprayed through an atomizing nozzle. The spraying amount was calculated as 2.7% of the dry weight of the bamboo-based filler. After spraying, mixing continued for 15 minutes to ensure uniform coating of the coupling agent on the surface of the bamboo-based material. Subsequently, the surface-modified bamboo-based material was transferred to a hot air drying oven and dried a second time at 100°C for 1.5 hours to complete the hydrolysis and condensation reaction of the silane coupling agent, allowing the coupling agent to form a stable organosiloxane monolayer on the surface of the bamboo-based material.
[0015] Resin pre-drying: Polylactic acid granules and polybutylene adipate / terephthalate granules were placed separately in an 80°C hot air drying oven and dried for 4 hours to reduce the moisture content to below 0.2% to avoid hydrolytic degradation during high-temperature processing. Bamboo nanocellulose suspension was freeze-dried before use to obtain flocculent dry powder with a moisture content of less than 5%.
[0016] Twin-screw extrusion blending and granulation: A co-rotating twin-screw extruder with a screw diameter of 35 mm and an aspect ratio of 36 is used. Pre-dried polylactic acid granules, polybutylene adipate / terephthalate granules, glycidyl methacrylate, and antioxidants are added to the extruder through the main feed port. Modified bamboo micro-powder, modified bamboo short fibers, bamboo nanocellulose powder, and heat stabilizers are added through the side feed port. The extruder temperatures are set as follows: Zone 1 165°C, Zone 2 178°C, Zone 3 185°C, Zone 4 180°C, and the die head 175°C. The screw speed is set to 250 rpm, and the main feed speed is matched with the screw speed to ensure a stable material filling rate. After being extruded through the die head, the molten material enters a cooling water tank at 30°C for water cooling and stretching, and then is cut into granules with a length of approximately 3 mm by a pelletizer. The pellets were dried in a 65°C hot air drying oven for 1.5 hours to remove residual moisture from the surface, thus obtaining bamboo-based spinning material masterbatch.
[0017] Melt spinning: Bamboo-based spinning material masterbatch is fed into a single-screw melt spinning machine. The spinning temperature is set to 180°C, and the metering pump speed is adjusted according to the target fineness. The spinneret orifice diameter is 0.3 mm, and the aspect ratio is 4. After the nascent fibers are cooled and solidified by ring blowing, they enter the drawing system. The temperature of the first-stage drawing roller is 65°C, and the draw ratio is 3.5; the temperature of the second-stage drawing roller is 85°C, and the draw ratio is 1.3. The total draw ratio is 4.55. The short fiber winding speed is 400 m / min. After drawing and setting, the fibers are crimped and cut to obtain bamboo-based polylactic acid short fibers with a length of 38 mm.
[0018] The prepared bamboo-based spinning material masterbatch had a melt index of 28 g / 10min (190°C / 2.16kg), indicating that the material has good melt flowability and meets the rheological requirements of spinning processing. The density of the masterbatch was 1.28 g / cm3. Differential scanning calorimetry (DSC) results showed that the material had a glass transition temperature of 58°C, a cold crystallization temperature of 95°C, a melting temperature of 172°C, and a crystallinity of 42%, which was 7 percentage points higher than that of pure polylactic acid (35%). This indicates that the heterogeneous nucleation effect of bamboo nanocellulose significantly accelerated the crystallization process of polylactic acid.
[0019] The prepared bamboo-based polylactic acid (PLA) staple fiber has a linear density of 2.2 dBT, a tensile strength of 38.5 MPa, an elongation at break of 28.3%, and an initial modulus of 3.8 GPa. The fiber has a moisture regain of 1.2%, exhibiting good hygroscopicity. The fiber surface has a soft and delicate feel with no obvious irritation, comparable to the tactile feel of petroleum-based polyester staple fiber.
[0020] The stability of the spinning process in Example 1 was monitored and recorded. During 8 hours of continuous spinning operation, the spinning pressure fluctuation ranged from 8.2 to 9.1 MPa, with a fluctuation amplitude not exceeding 10%, indicating good rheological uniformity of the melt. The fiber breakage rate was 0.3 times per thousand spindles, far lower than the 2.5 times per thousand spindles for pure polylactic acid spinning, indicating a significant improvement in spinning stability. Scanning electron microscopy analysis of the fiber cross-section showed that bamboo micropowder and bamboo short fibers were uniformly dispersed in the polylactic acid matrix, with no obvious agglomeration observed. The interface between the bamboo-based filler and the matrix was tightly bonded, with no debonding voids. Energy dispersive X-ray spectroscopy analysis detected characteristic peaks of silicon on the surface of the bamboo-based filler, confirming that the aminosilane coupling agent had been successfully anchored on the surface of the bamboo-based material.
[0021] Thermogravimetric analysis (TGA) was performed on the fibers from Example 1. The fibers were heated from room temperature to 600°C at a rate of 10°C / min under a nitrogen atmosphere. The results showed that the initial decomposition temperature of the fibers was 285°C, the maximum decomposition rate corresponded to a temperature of 342°C, and the residual carbon content at 600°C was 8.7%. Compared with the initial decomposition temperature of 283°C for pure polylactic acid fibers, the thermal stability of the bamboo-based spun fibers did not show significant deterioration, indicating that the introduction of bamboo-based fillers and interface modification effectively avoided degradation problems during thermal processing.
[0022] Dynamic mechanical analysis was performed on the fibers of Example 1. A tensile mode was used with a frequency of 1 Hz, a temperature range of -20°C to 150°C, and a heating rate of 3°C / min. The results showed that the storage modulus of the bamboo-based spun fiber was 4.2 GPa at 30°C, which was 16.7% higher than the 3.6 GPa of pure polylactic acid (PLA) fiber. The peak temperature of the loss factor was 62°C, which was 5°C higher than the 57°C of pure PLA, indicating that the introduction of bamboo-based filler restricted the degree of freedom of movement of the PLA molecular chains and increased the upper limit of the material's operating temperature.
[0023] The masterbatch from Example 1 was tested using a rotational rheometer. Frequency scanning was performed at 190°C, with angular frequencies ranging from 0.1 to 100 radians / second. The results showed that the zero-shear viscosity of the masterbatch was 850 Pa·s, significantly higher than that of pure polylactic acid (PLA) at 320 Pa·s, indicating that the three-dimensional network structure of bamboo nanocellulose and the orientation effect of bamboo short fibers enhanced the elastic response of the melt. In the high-frequency region (greater than 10 radians / second), the crossover frequency of storage modulus and loss modulus was 25 radians / second, corresponding to a characteristic relaxation time of 0.04 seconds, indicating that the material has good processability within the typical shear rate range of spinning.
[0024] Example 2 This embodiment provides a bamboo-based spinning material solution with a high polylactic acid content.
[0025] The formula composition by weight is as follows: 65 parts polylactic acid, 15 parts modified bamboo micro powder, 5 parts modified bamboo short fiber, 8 parts poly(butylene adipate / terephthalate), 1.0 part glycidyl methacrylate, 0.6 parts aminosilane coupling agent KH-550, 0.2 parts antioxidant, 0.3 parts heat stabilizer, and 1 part bamboo nanocellulose.
[0026] The surface modification process for the bamboo-based filler is the same as in Example 1, but the amount of KH-550 is adjusted to 3.0% of the dry weight of the bamboo-based filler. The resin pre-drying process is the same as in Example 1.
[0027] The twin-screw extrusion blending and granulation process parameters were adjusted as follows: Zone 1 160°C, Zone 2 175°C, Zone 3 182°C, Zone 4 178°C, and die head 172°C. The screw speed was 220 rpm. The remaining operating steps were the same as in Example 1.
[0028] The melt spinning temperature was adjusted to 178°C. The first-stage drawing temperature was 62°C with a draw ratio of 3.0; the second-stage drawing temperature was 82°C with a draw ratio of 1.2. The total draw ratio was 3.6. The filament winding speed was 1000 m / min to prepare bamboo-based polylactic acid filaments.
[0029] The melt index of the prepared masterbatch was 35 g / 10min (190°C / 2.16kg). Differential scanning calorimetry analysis showed a crystallinity of 39%. The linear density of the produced filament was 1.8 dBT, the tensile strength was 36.2 MPa, the elongation at break was 24.6%, and the initial modulus was 4.1 GPa. The fiber had a soft hand feel and good luster.
[0030] Example 3 This embodiment provides a spinning material scheme with a high bamboo-based filler content to verify the spinning feasibility under the upper limit boundary conditions of bamboo-based components.
[0031] The formula composition by weight is as follows: 45 parts polylactic acid, 30 parts modified bamboo micro powder, 10 parts modified bamboo short fiber, 15 parts poly(butylene adipate / terephthalate), 2.5 parts glycidyl methacrylate, 1.2 parts aminosilane coupling agent KH-550, 0.4 parts antioxidant, 0.6 parts heat stabilizer, and 4 parts bamboo nanocellulose.
[0032] The surface modification process for bamboo-based fillers was the same as in Example 1, but the amount of KH-550 was adjusted to 3.0% of the dry weight of the bamboo-based filler, and the spraying and mixing time in the high-speed mixer was extended to 20 minutes to ensure sufficient coating of the coupling agent under high filling conditions. The secondary drying temperature was increased to 105°C, and the drying time was extended to 2 hours.
[0033] The twin-screw extrusion blending and granulation process parameters were adjusted to: Zone 1 170°C, Zone 2 182°C, Zone 3 190°C, Zone 4 185°C, and die head 180°C. The screw speed was increased to 280 rpm to enhance the shearing and mixing effect. A loss-in-weight feeder was used for side feeding to ensure the uniform and stable addition of bamboo-based fillers. The cooling water temperature was controlled at 28°C.
[0034] The melt spinning temperature was adjusted to 185°C. The spinneret orifice diameter was enlarged to 0.4 mm to accommodate spinning requirements of materials with higher filler content. The first-stage drafting temperature was 68°C with a draft ratio of 3.0; the second-stage drafting temperature was 88°C with a draft ratio of 1.2. The overall draft ratio was 3.6. The short fiber winding speed was 350 m / min.
[0035] The melt index of the prepared masterbatch was 22 g / 10min (190°C / 2.16 kg), which was lower than that of Example 1, but still within the spinnable range. Differential scanning calorimetry (DSC) results showed a crystallinity of 45%, the highest among the three examples, indicating that the heterogeneous nucleation effect of high-content bamboo nanocellulose further enhanced the crystallinity of polylactic acid. The prepared short fibers had a linear density of 2.8 dBT, a tensile strength of 34.1 MPa, an elongation at break of 22.5%, and an initial modulus of 4.3 GPa. The fiber stiffness increased slightly but still maintained good softness, and the biomass content reached over 58%.
[0036] Comparative Example 1 This comparative example provides a bamboo-based material solution without poly(butylene adipate) / butyl terephthalate (PET) toughening components to verify the key role of toughening components in spinning performance.
[0037] The formula composition by weight is as follows: 65 parts polylactic acid, 25 parts modified bamboo micro powder, 5 parts modified bamboo short fiber, 1.5 parts glycidyl methacrylate, 0.8 parts aminosilane coupling agent KH-550, 0.3 parts antioxidant, 0.4 parts heat stabilizer, and 2 parts bamboo nanocellulose. Poly(butylene adipate) / butylene terephthalate is not added.
[0038] The preparation process was the same as in Example 1. The melt index of the prepared masterbatch was 18 g / 10min (190°C / 2.16kg), indicating a significant decrease in melt flowability. During melt spinning, the spinning temperature needed to be increased to 190°C to maintain spinnability, but the fibers frequently experienced brittle fracture during the drawing process, making stable continuous spinning impossible. The tensile strength of the barely collected fiber sample was 32.0 MPa, but the elongation at break was only 8.5%, far below the requirements for textile fiber use. The fiber felt hard and brittle, and had a rough texture.
[0039] Comparative Example 2 This comparative example provides a bamboo-based material scheme without bamboo nanocellulose to verify the effect of bamboo nanocellulose on crystallization behavior and spinning stability.
[0040] The formula composition by weight is as follows: 55 parts polylactic acid, 27 parts modified bamboo micro powder, 5 parts modified bamboo short fiber, 10 parts polybutylene adipate / terephthalate, 1.5 parts glycidyl methacrylate, 0.9 parts aminosilane coupling agent KH-550, 0.3 parts antioxidant, and 0.4 parts heat stabilizer. No bamboo nanocellulose is added.
[0041] The preparation process was the same as in Example 1. Differential scanning calorimetry analysis of the prepared masterbatch showed a crystallinity of only 33%, a decrease of 9 percentage points compared to Example 1, indicating that the lack of heterogeneous nucleation effect from bamboo nanocellulose led to a significant decrease in the crystallization rate and crystallinity of polylactic acid. During spinning, the cooling and solidification rate of the fibers was slow, and the nascent fibers were not sufficiently shaped in the ring-blown cooling zone, resulting in fiber adhesion and poor spinning stability. The tensile strength of the prepared fibers was 33.8 MPa, and the elongation at break was 21.2%, showing a decrease in mechanical properties compared to Example 1.
[0042] Comparative Example 3 This comparative example provides a bamboo-based material solution without silane coupling agent surface modification to verify the contribution of interface modification engineering to material properties.
[0043] The formulation composition is exactly the same as in Example 1, but the bamboo micro powder and bamboo short fiber are not subjected to KH-550 surface modification treatment, and are used directly after being dried at 105°C.
[0044] The preparation process was the same as in Example 1. Because the bamboo-based filler surface was not treated with a coupling agent, the interfacial bonding between its hydrophilic surface and the hydrophobic polylactic acid matrix was extremely weak. The torque fluctuation of the material during twin-screw extrusion was significantly increased, indicating poor dispersion uniformity of the bamboo-based filler in the matrix. Obvious white bamboo powder agglomerates were present in the prepared masterbatch. During spinning, these agglomeration defects became stress concentration sources, leading to frequent filament breakage. The tensile strength of the resulting fiber was only 26.3 MPa, a decrease of 31.7% compared to Example 1, and the elongation at break was 15.8%, a decrease of 44.2%. Scanning electron microscopy observation of the fiber cross-section showed obvious interfacial debonding between the bamboo-based filler and the polylactic acid matrix, confirming the decisive role of silane coupling agent surface modification in improving interfacial bonding.
[0045] Comparative Example 4 This comparative example provides a bamboo-based material scheme without glycidyl methacrylate compatibilizer to verify the necessity of reactive compatibilization of the interface between polylactic acid and poly(adipate) / butyl terephthalate.
[0046] The formulation is the same as in Example 1, but glycidyl methacrylate is not added.
[0047] The preparation process was the same as in Example 1. Due to the lack of a reactive compatibility component, the interfacial tension between polylactic acid (PLA) and poly(butylene adipate / terephthalate) was high, resulting in larger dispersed phase droplets of PDA forming within the PLA matrix. The dispersed phase particle size increased from 0.5–1.2 μm in Example 1 to 2.5–5.0 μm. This coarse two-phase morphology significantly reduced the toughening effect of the material. The tensile strength of the prepared fiber was 31.5 MPa, and the elongation at break was 16.3%, representing decreases of 18.2% and 42.4%, respectively, compared to Example 1.
[0048] Comparative Example 5 This comparative example provides pure polylactic acid spun fiber as a blank benchmark for comprehensive performance comparison with the bamboo-based spun fiber of the present invention.
[0049] Polylactic acid granules of the same grade as in Example 1 were used, without any bamboo-based fillers or modifying agents. After drying at 80°C for 4 hours, they were directly melt-spun. The spinning temperature was 185°C, the first-stage drawing temperature was 60°C with a draw ratio of 3.5, and the second-stage drawing temperature was 80°C with a draw ratio of 1.5. The resulting fiber had a tensile strength of 40.2 MPa and an elongation at break of only 12.8%. The fiber was stiff and brittle, and easily broke when bent. Differential scanning calorimetry analysis showed a crystallinity of 35%.
[0050] The breakage rate of pure polylactic acid (PLA) fiber during spinning was 2.5 times per thousand spindles, significantly higher than the 0.3 times per thousand spindles in Example 1. This is because the melt strength of pure PLA is insufficient, making it prone to melt fracture under high-speed drawing conditions. Furthermore, the slow crystallization rate of PLA results in insufficient solidification of the nascent fibers in the cooling zone, leading to brittle fracture of the amorphous regions of the fibers under drawing force. The bending stiffness of pure PLA fiber, as tested, was 8.2 millinewtons per square centimeter, 70.8% higher than that of the fiber in Example 1 (4.8 millinewtons per square centimeter), further confirming the key contributions of the addition of poly(adipic acid) / butyl terephthalate (PET) toughening components and the construction of the bamboo nanocellulose network structure to improving fiber softness. The cumulative degradation rate of pure PLA fiber after 180 days of composting degradation testing was 85.2%, lower than the 91.3% in Example 1, indicating that the introduction of bamboo-based fillers indeed accelerated the degradation process of the PLA matrix by forming microporous channels.
[0051] The detection method is as follows: Melt flow index test: According to GB / T 3682.1—2018 standard, the melt flow rate tester was used to test under the conditions of 190°C and 2.16 kg load, and the mass of melt passing through the standard die within 10 minutes was recorded.
[0052] Mechanical property testing: The tensile strength and elongation at break of the fiber were tested according to GB / T 14344—2022 standard using a universal testing machine with a clamping distance of 20 mm and a tensile speed of 20 mm / min. Each group consisted of no less than 20 fiber samples, and the arithmetic mean was taken.
[0053] Thermal analysis tests: Differential scanning calorimetry (DSC) was used for testing under a nitrogen atmosphere. The heating program was as follows: the temperature was first increased from 25°C to 200°C at a rate of 10°C / min, held at this temperature for 5 minutes to eliminate thermal history, then decreased to 25°C at a rate of 10°C / min, and finally increased again to 200°C at a rate of 10°C / min. The glass transition temperature, cold crystallization temperature, melting temperature, and crystallinity were calculated based on the data from the second heating curve.
[0054] Microscopic morphology observation: The cross-section and surface morphology of the fibers were observed using a scanning electron microscope. After the samples were fractured in liquid nitrogen, they were sputter-coated with gold at an accelerating voltage of 10 kV.
[0055] Moisture regain test: In accordance with GB / T 6503—2017 standard, after the fiber sample is equilibrated under standard atmospheric conditions (temperature 20°C±2°C, relative humidity 65%±3%) for 24 hours, the wet weight is weighed, and then dried at 105°C±2°C to constant weight, the dry weight is weighed, and the moisture regain is calculated.
[0056] Biodegradation performance test: In accordance with GB / T 19277.1—2011 standard, a biodegradation test was conducted for 180 days under controlled composting conditions (temperature 58°C±2°C, moisture content 50%~55%). The biodegradation rate was calculated by measuring the cumulative amount of carbon dioxide released.
[0057] Fiber crimp performance test: The number of crimps, crimp rate, and crimp recovery rate of the fibers were determined using a fiber crimp elasticity tester according to GB / T 14338—2022 standard. Approximately 50 mg of fiber bundle was pretreated under standard atmospheric conditions for 24 hours before testing. The fiber crimp number in Example 1 was 12 crimps / 25 mm, the crimp rate was 13.2%, and the crimp recovery rate was 78.5%, meeting the basic requirements for fiber crimp performance in spinning processing.
[0058] Fiber cross-sectional morphology analysis: The fiber samples were fractured in liquid nitrogen, and cross-sectional samples were prepared using a cryostat. The phase distribution of the fiber cross-section was characterized using atomic force microscopy in impact mode. The analysis results showed that in the fiber cross-section of Example 1, the poly(adipate adipate) / butyl terephthalate dispersed phase was uniformly distributed in the polylactic acid continuous phase as spherical droplets of 0.5-1.2 μm. The bamboo microparticles were completely coated by the polylactic acid matrix, and no voids or cracks were observed at the interface. The bamboo short fibers were oriented along the fiber axis with an orientation degree of over 0.82, which is beneficial to the improvement of the axial mechanical properties of the fibers.
[0059] Wide-angle X-ray diffraction test: The fiber samples were analyzed for crystal structure using an X-ray diffractometer. The scanning range was 5°~40°, and the scanning rate was 2° / min. The fiber in Example 1 showed typical polylactic acid (PLA) diffraction peaks at 2θ of 16.7° and 19.1°, corresponding to the (110) / (200) and (203) crystal planes of the α-crystal form of PLA. The half-width at half-maximum (FWHM) of the diffraction peaks was significantly smaller than that of pure PLA fibers, indicating that the heterogeneous nucleation effect of bamboo nanocellulose resulted in larger grain sizes and higher crystallinity of PLA crystals. A (200) crystal plane diffraction peak of bamboo cellulose appeared near 2θ of 22.5°. Although the intensity was weak, it was still identifiable, confirming that the cellulose crystal structure of the bamboo-based filler was basically preserved during processing.
[0060] The performance test results of all the above embodiments and comparative examples are summarized in Tables 1 and 2 for systematic comparative analysis.
[0061] Table 1 Comparison of mechanical properties of masterbatch and fiber in each embodiment and comparative example
[0062] Note: Melt index test conditions are 190°C / 2.16kg; “—” indicates that due to frequent filament breakage, it was impossible to obtain a complete fiber sample for testing.
[0063] Table 2 Comparison of thermal properties, degradation properties, and spinning process parameters between each embodiment and the comparative example
[0064] Note: Comparative Example 1 could not obtain complete fibers for degradation and bending stiffness testing because it could not be spun stably.
[0065] Table 3 Comparison of performance between Example 1 fiber and ordinary polyester staple fiber
[0066] As shown in Table 1, the tensile strength of the bamboo-based spun fibers in Examples 1 to 3 ranges from 34.1 to 38.5 MPa, and the elongation at break ranges from 22.5% to 28.3%, all meeting the mechanical property standards for textile fibers. Among the three examples, Example 1 exhibits the best overall performance, achieving the ideal effect of "increased toughness without reduced strength" through the combination of a tensile strength of 38.5 MPa and an elongation at break of 28.3%. Example 2 increased the polylactic acid content to 65 parts, resulting in a fiber tensile strength of 36.2 MPa, an elongation at break of 24.6%, and a melt index of 35 g / 10 min, exhibiting the best flowability and suitability for high-speed filament spinning. Example 3 increased the total amount of bamboo-based filler to 40 parts. Although the mechanical properties decreased slightly, the biomass content reached over 58%, and the crystallinity was as high as 45%, making it suitable for green textiles with specific requirements for biomass content.
[0067] The data from Comparative Examples 1 to 5 systematically reveal the irreplaceable role of each key technical feature of the present invention. Comparative Example 1, lacking the poly(butylene adipate) / poly(terephthalate) toughening component, experienced a sharp decrease in elongation at break to 8.5%, only 30.0% of Example 1, and frequent fiber breakage during spinning prevented continuous production, directly demonstrating that the toughening component is a prerequisite for achieving spinning-grade toughness. Comparative Example 2, lacking bamboo nanocellulose, saw its crystallinity decrease from 42% in Example 1 to 33%, a reduction of 21.4%, while the fiber breakage rate increased from 0.3 times / thousand spindles to 1.8 times / thousand spindles, a five-fold increase. Simultaneously, fiber adhesion occurred, indicating that the heterogeneous nucleation function of bamboo nanocellulose is indispensable for ensuring spinning stability and fiber setting quality. Comparative Example 3, without silane coupling agent surface modification, saw its fiber tensile strength decrease from 38.5 MPa to 26.3 MPa, a reduction of 31.7%, and its elongation at break decrease from 28.3% to 15.8%, a reduction of 44.2%. Furthermore, its fiber breakage rate reached a high of 3.2 times / thousand spindles, the highest among all samples, indicating that interfacial chemical bridging is fundamental to the effective transfer of mechanical properties. Comparative Example 4, without glycidyl methacrylate reactive compatibilizer, saw its elongation at break decrease from 28.3% to 16.3%, a reduction of 42.4%. Although the tensile strength of 31.5 MPa was still acceptable, the significant decrease in toughness demonstrates that effective compatibilization at the two-phase interface is crucial for the transfer of toughening effects.
[0068] As shown in Table 2, the initial decomposition temperatures of the fibers in Examples 1 to 3 were in the range of 280–285°C, all more than 90°C higher than the spinning processing temperature (175–190°C). This indicates that the introduction of bamboo-based fillers and interface modification treatment did not lead to a deterioration in the thermal stability of the material, and the processing safety margin was sufficient. The fiber breakage rate data further quantified the differences in spinning stability: the fiber breakage rate in Example 1 was 0.3 times / thousand spindles, which was 88% lower than the 2.5 times / thousand spindles of pure polylactic acid in Comparative Example 5. This significant improvement was attributed to the synergistic effect of bamboo nanocellulose enhancing melt elasticity, glycidyl methacrylate improving the two-phase interface, and poly(adipic acid) / butyl terephthalate providing toughness reserves. Bending stiffness data showed that the bending stiffness of the fiber in Example 1 was 4.8 mN·cm. 2 This is lower than the 8.2 mN·cm of pure polylactic acid fiber in Comparative Example 5. 2 The decrease reached 41.5%, which quantitatively verified that the fiber of the present invention has a significantly better softness than pure polylactic acid fiber.
[0069] Regarding biodegradability, the cumulative degradation rates of Examples 1 to 3 under controlled composting conditions over 180 days were 91.3%, 89.5%, and 93.7%, respectively, all reaching or approaching the 90% degradation rate requirement specified in GB / T 19277.1—2011. Example 3 exhibited the highest degradation rate (93.7%), directly related to its highest bamboo-based filler content (40 parts): cellulose and hemicellulose in the bamboo-based component preferentially degraded under the action of composting microorganisms, forming numerous microporous channels, significantly accelerating the subsequent hydrolytic degradation of the polylactic acid matrix. The 180-day degradation rate of pure polylactic acid fiber in Comparative Example 5 was 85.2%, 6.1 percentage points lower than that of Example 1, further confirming the degradation-promoting effect of the bamboo-based filler.
[0070] As shown in Table 3, after a comprehensive comparison with ordinary polyester staple fiber, the tensile strength of the fiber in Example 1 reached 96.3% of the lower limit of polyester, and the elongation at break of 28.3% was within the performance range of polyester (25%~40%). The initial modulus of 3.8 GPa was close to the lower limit of polyester (4 GPa). In terms of moisture absorption and softness, the moisture regain of bamboo-based spun fiber (1.2%) was significantly higher than that of polyester (0.4%~0.5%), and the bending stiffness was 4.8 mN·cm. 2 Lower than polyester by 5.0~7.0 mN·cm 2 This indicates that the fiber of this invention is superior to polyester in terms of wearing comfort. The most prominent differentiating advantage lies in its complete biodegradability: a 91.3% compost degradation rate after 180 days, while polyester is almost non-degradable in the natural environment. In summary, the bamboo-based spun fiber of this invention possesses the comprehensive performance foundation to replace ordinary polyester staple fiber, and has significant differentiated competitive advantages in terms of moisture absorption, softness, and environmental friendliness.
[0071] Further comparative analysis was conducted on the comprehensive performance evaluation index of each embodiment and comparative example. Using typical performance indicators of pure polyester staple fiber (tensile strength 40-50 MPa, elongation at break 25-40%, initial modulus 4-8 GPa) as benchmarks, the tensile strength of the fiber in Example 1 reached 96.3% of the lower limit of polyester, the elongation at break was in the lower-middle range of polyester, and the initial modulus of 3.8 GPa was close to the lower limit of polyester. In summary, the bamboo-based spun fiber of Example 1 has basically reached the performance threshold for replacing ordinary polyester staple fiber and can meet the routine usage requirements of clothing fabrics, home textiles, and industrial textiles. Especially in terms of softness and skin-friendliness, due to the natural antibacterial properties of bamboo-based materials and the weakly acidic surface characteristics of polylactic acid, bamboo-based spun fiber exhibits superior comfort compared to polyester in close-fitting applications.
[0072] In Example 2, with the polylactic acid content increased to 65 parts, the fiber tensile strength still reached 36.2 MPa, and the elongation at break was 24.6%, verifying the robustness and adjustability of the formulation system of the present invention within the range of component ratio changes. In Example 3, the total amount of bamboo-based filler was increased to 40 parts, and the polylactic acid content was reduced to 45 parts. The fiber tensile strength was 34.1 MPa, and the elongation at break was 22.5%. Although the mechanical properties decreased slightly, they still met the basic requirements for textile fibers, and the biomass content was significantly increased.
[0073] Comparative Examples 1 to 4 verified the irreplaceable role of four key technical elements in material performance: poly(adipate-butyl terephthalate) toughening component, bamboo nanocellulose, silane coupling agent surface modification, and glycidyl methacrylate reaction compatibility. Specifically, Comparative Example 1, lacking the toughening component, resulted in an elongation at break of only 8.5% and unstable spinning, demonstrating that poly(adipate-butyl terephthalate) is crucial for achieving spinning-grade toughness. Comparative Example 2, lacking bamboo nanocellulose, resulted in a decrease in crystallinity from 42% to 33% and a decline in spinning stability, proving that the heterogeneous nucleation effect of bamboo nanocellulose is a key factor in ensuring spinning processing stability. Comparative Example 3, without coupling agent treatment, resulted in a 31.7% decrease in tensile strength and frequent filament breakage, demonstrating the decisive significance of interfacial chemical bridging for the transfer of mechanical properties. Comparative Example 4, lacking a reactive compatibilizer, resulted in an increase in the particle size of the two dispersed phases and a decrease in the elongation at break of 42.4%, demonstrating that reactive compatibilization is a necessary condition for achieving efficient compatibilization of polylactic acid and poly(adipate) / butyl terephthalate.
[0074] The superior comprehensive performance of the bamboo-based spinning material of this invention originates from the gradient interface enhancement effect of multi-morphological bamboo-based fillers, the synergistic effect of dual interface modification engineering, and the deep coupling mechanism among bamboo nanocellulose on the crystallization behavior of polylactic acid.
[0075] At the gradient interface reinforcement level, bamboo micropowder is uniformly dispersed in the polylactic acid (PLA) matrix at the nano-microscale, acting as rigid particles to fill the free volume between the matrix molecular chains, improving the material's elastic modulus and dimensional stability. Simultaneously, it acts as stress dispersion nodes under stress, delaying crack initiation. Bamboo short fibers are oriented along the spinning direction at the millimeter scale. Their high aspect ratio allows them to bear the main stress transmission function under tensile loads, absorbing a large amount of fracture energy through fiber pull-out and fiber bridging mechanisms, significantly improving the fiber's fracture toughness. Bamboo nanocellulose forms a three-dimensional network entanglement structure in the PLA matrix at the nanoscale. On one hand, it acts as physical crosslinking points to enhance the melt elasticity of the matrix, improving melt strength and spinnability during melt spinning. On the other hand, the numerous hydroxyl groups on its surface act as heterogeneous nucleation sites, lowering the nucleation energy barrier for PLA crystallization, accelerating crystal growth, increasing crystallinity and crystallization rate, enabling rapid fiber setting during cooling, and reducing fiber adhesion. These three scales of bamboo-based components constitute a continuous reinforcement network from nanometer to millimeter, achieving full-scale optimization of mechanical properties.
[0076] At the interface modification level, the aminosilane coupling agent KH-550 contains two reactive terminals: an amino functional group and a siloxane group. The siloxane group, after hydrolysis, generates a silanol group, which undergoes a dehydration condensation reaction with the cellulose hydroxyl groups on the surface of the bamboo-based material to form a stable siloxane covalent bond, anchoring the coupling agent to the bamboo-based material surface. The amino terminal then undergoes a nucleophilic reaction with the carboxyl terminus and ester bond on the polylactic acid (PLA) molecular chain at the melt processing temperature, establishing a chemical bridge between the bamboo-based filler and the PLA matrix. The epoxy functional group of glycidyl methacrylate undergoes a ring-opening reaction under the high temperature and high shear conditions during melt extrusion, forming ester bonds with the carboxyl terminus of PLA and the hydroxyl terminus of poly(adipate adipate / butyl terephthalate), respectively, generating an in-situ PLA-glycidyl methacrylate-poly(adipate adipate / butyl terephthalate) graft copolymer. This graft copolymer accumulates at the interface between the two phases, reducing interfacial tension and promoting the formation of submicron-sized, fine, and uniformly dispersed phases of poly(adipate adipate / butyl terephthalate) within the polylactic acid matrix. These fine dispersed phase droplets absorb a large amount of impact energy under stress through cavitation and matrix shear yielding mechanisms, thus achieving highly efficient toughening.
[0077] At the crystallization control level, the high specific surface area and abundant hydroxyl groups of bamboo nanocellulose provide a large number of heterogeneous nucleation sites for polylactic acid (PLA) crystal nucleation. Compared with Comparative Example 2 without bamboo nanocellulose, the crystallinity of Example 1 increased from 33% to 42%, and the crystallization half-life was shortened from 15 minutes for pure PLA to 3.5 minutes, indicating that bamboo nanocellulose increased the crystallization rate of PLA by approximately four times. Rapid crystallization not only improves the cooling and setting efficiency and spinning stability of the fiber, but also makes the crystal structure of PLA more perfect, with more uniform and finer grain size, which is beneficial to improving the mechanical properties and dimensional stability of the fiber. At the same time, the high crystallinity increases the heat distortion temperature of the fiber, giving it better heat resistance in subsequent heat setting and dyeing and finishing processes.
[0078] The deep coupling of the aforementioned triple synergistic mechanism enables the bamboo-based spinning material of this invention to significantly improve its elongation at break and toughness while maintaining the high strength of the polylactic acid matrix. This achieves stable and controllable spinning processing, and the overall performance of the produced fiber is comparable to that of petroleum-based polyester. The synergistic effect between the various technical features exceeds the expected effect of simple superposition, constituting the unexpected technical effect of this invention compared to the prior art.
[0079] Further analysis from the perspective of interfacial chemical reaction kinetics reveals that the aminosilane coupling agent KH-550 first undergoes hydrolysis in ethanol solution, where the three methoxy groups hydrolyze to silanol groups. These active silanol groups then undergo dehydration condensation with the primary and secondary hydroxyl groups on the bamboo cellulose surface under secondary drying conditions at 100–105°C. This condensation reaction exhibits high efficiency under acidic conditions (the weakly acidic environment of the bamboo-based material surface), with the resulting siloxane covalent bond energy being approximately 452 kJ / mol, significantly higher than the 20–40 kJ / mol of hydrogen bonds. Therefore, the coupling agent demonstrates excellent durability and solvent resistance when anchored on the bamboo-based material surface. During melt processing, the amino terminus forms a chemical bond with the polylactic acid matrix primarily through two pathways: first, the amino group undergoes amidation with the carboxyl group at the end of the polylactic acid chain to form an amide bond; second, the amino group undergoes ammonolysis with the ester bonds on the polylactic acid chain to form new amide bonds and free hydroxyl groups. Both reactions have moderate reaction rates within the spinning processing temperature window of 175~190°C, which can ensure the effective establishment of interfacial chemical bridging without causing excessive degradation of polylactic acid molecular chains.
[0080] The reactivity of the epoxy functional groups of glycidyl methacrylate under the high temperature and high shear conditions of melt extrusion is the core chemical basis for the efficient compatibilization achieved in this invention. The reaction between the epoxy group and the terminal carboxyl group of polylactic acid is a nucleophilic ring-opening mechanism, where the carboxyl group oxygen atom attacks the less sterically hindered carbon atom on the epoxy ring, opening the three-membered ring to form a hydroxyl ester bond. Simultaneously, the reaction between the epoxy group and the terminal hydroxyl group of poly(adipate adipate / butyl terephthalate) is a base-catalyzed ring-opening mechanism, and the reaction rate is further increased under the Lewis acid catalysis of zinc stearate in the heat stabilizer. The in-situ generated graft copolymer molecular chains have segments at both ends compatible with polylactic acid and poly(adipate adipate / butyl terephthalate), thus acting as surfactants at the two-phase interface, reducing interfacial tension, stabilizing the dispersed phase morphology, and preventing the poly(adipate adipate / butyl terephthalate) dispersed phase from coalescence and coarsening during subsequent spinning processing.
[0081] The regulatory mechanism of bamboo nanocellulose on the crystallization behavior of polylactic acid (PLA) can be explained by the classical heterogeneous nucleation theory. Bamboo nanocellulose fibers have a diameter of 3–10 nm and a specific surface area as high as 200–500 m² / g. The lattice parameters of the cellulose on its surface match those of the PLA crystals to a certain degree. This lattice matching reduces the interfacial energy between the nucleus and the substrate, thereby lowering the critical nucleation free energy. According to the classical nucleation theory, the reduction in the critical nucleation free energy directly leads to an exponential increase in the nucleation rate. The experimental results in Example 1, which shortened the crystallization half-life of PLA from approximately 15 minutes for pure PLA to approximately 3.5 minutes, confirm the above theoretical analysis. Furthermore, the high aspect ratio of bamboo nanocellulose causes it to align along the flow direction during melt flow. This alignment provides a linear template for the epitaxial growth of PLA crystals, promoting the directional growth of PLA crystals along the fiber axis, forming a tandem crystal structure, and further improving the axial mechanical properties of the fiber.
[0082] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the invention by those skilled in the art. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the invention should be included within the scope of the claims.
Claims
1. A bamboo-based spinning material, characterized in that, The spinning material comprises, by weight, 45-65 parts polylactic acid, 20-40 parts modified bamboo-based filler, 5-15 parts poly(butylene adipate / terephthalate), 1-3 parts glycidyl methacrylate, 0.5-1.5 parts aminosilane coupling agent, 0.1-0.5 parts antioxidant, 0.2-0.8 parts heat stabilizer, and 1-4 parts bamboo nanocellulose; the modified bamboo-based filler is a mixture of bamboo micropowder and bamboo short fibers surface-treated with aminosilane coupling agent; the bamboo micropowder has a particle size of 10-20 micrometers; the bamboo short fibers have a length of 1-3 millimeters and a diameter of 10-50 micrometers; the bamboo nanocellulose has a particle size of no more than 100 nanometers and a solid content of 10%-20%; and the polylactic acid has a melt index of 30-60 g / 10min.
2. The bamboo-based spinning material according to claim 1, characterized in that, The weight ratio of bamboo micro powder to bamboo short fiber in the modified bamboo-based filler is (3~6):
1.
3. The bamboo-based spinning material according to claim 1, characterized in that, The aminosilane coupling agent is KH-550, and its dosage is 2% to 4% of the dry weight of the modified bamboo-based filler.
4. The bamboo-based spinning material according to claim 1, characterized in that, The grafting rate of the glycidyl methacrylate is not less than 1.5%.
5. The bamboo-based spinning material according to claim 1, characterized in that, The bamboo-based spinning material has a melt index of 20-40 g / 10min and a crystallinity of 38%-48% under conditions of 190°C and 2.16 kg load.
6. The method for preparing the bamboo-based spinning material according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1: Dry bamboo micro-powder and bamboo short fibers at 105-110°C for 2-4 hours to reduce the moisture content to below 3%. Then, spray an ethanol solution of aminosilane coupling agent into the mixture in a high-speed mixer at a speed of 600-1000 rpm for surface modification treatment. The spraying and mixing time is 10-20 minutes. Afterward, dry the mixture again at 100-105°C for 1-2 hours to obtain modified bamboo-based filler. Step 2: Dry polylactic acid granules and poly(adipate adipate / butyl terephthalate) granules at 80-85°C for 3-4 hours to reduce the moisture content to below 0.2%. Step 3: [The text abruptly ends here, likely due to an incomplete translation or missing information.] Butylene glycolate, glycidyl methacrylate, and antioxidants are fed into a co-rotating twin-screw extruder through the main feed port. The modified bamboo-based filler, bamboo nanocellulose, and heat stabilizer obtained in step one are added through the side feed port for melt extrusion blending and granulation. The extrusion temperature is 160~190°C, and the screw speed is 200~300 rpm. In step four, the masterbatch obtained in step three is melt-spun to prepare fibers. The spinning temperature is 175~190°C, the spinneret orifice diameter is 0.2~0.4 mm and the aspect ratio is 3~5, the first-stage drawing temperature is 60~70°C and the draw ratio is 3~4, and the second-stage drawing temperature is 80~90°C and the draw ratio is 1.2~1.
5.
7. The preparation method according to claim 6, characterized in that, The mass fraction of the ethanol solution of the aminosilane coupling agent mentioned in step one is 3% to 8%.
8. The preparation method according to claim 6, characterized in that, The length-to-diameter ratio of the co-rotating twin-screw extruder described in step three is 35~40, and the temperature settings for each zone of the extruder are: zone one 160~170°C, zone two 175~185°C, zone three 180~190°C, zone four 175~185°C, and die head 170~180°C.
9. The preparation method according to claim 6, characterized in that, In step three, the extruded molten material is granulated by water cooling with a cooling water temperature of 25-35°C. After granulation, it is dried at 60-70°C for 1-2 hours.
10. The preparation method according to claim 6, characterized in that, In step four, the fiber winding speed is: 800~1200 meters / minute for filaments and 300~500 meters / minute for short fibers.
Citation Information
Patent Citations
A method for producing polylactic acid bamboo powder composite modified material
CN105694400B
Bamboo-based degradable composite material for extruding and preparation method
CN106832989A
A stereocomposite interface-enhanced polylactic acid blend material and preparation method thereof
CN115028976B